Analisis Angkutan Kargo Antara ATR 72-600 Passenger, ATR 72-600 Freighter Dan ATR 72-600 Converted Pada Rute Makassar – Kendari - Somadi, Ridho Misbahudin; Arifin, Mufti; Yuniarti, Endah (Jurnal Teknologi Kedirgantaraan, 2022)
Delivery of goods (cargo) between islands or between countries is faster by air transportation. Air cargo can use passenger aircraft (bulk cargo), Air freighters, Combined air freighters, Converted freighters for the same type of aircraft, such as ATR 72-600. This study discusses fuel consumption, comparison of payload capacity, and comparison of fuel consumption per payload of ATR 72-600 aircraft for the Makassar – Kendari route. namely the ATR 72-600, ATR 72-600 Freighter and ATR 72-600 Converted aircraft. The method used is a quantitative method. The results of the calculation using the flight crew operation manual for ATR 72-600 passenger fuel carried 1.143,4 kg and fuel consumption of 609.4 kg, ATR 72-600 Freighter and Converted aircraft carried 1.210,3 kg of fuel and 613,3 fuel consumption, 4 kg. Fuel costs per kg of cargo, ATR 72-600 Passenger aircraft are more expensive, namely Rp. 1,279 per kg, freighter Rp. 1,136 per kg, converted bulk cargo Rp. 1,175 per kg, Converted Large cargo door Rp. 1,202 per kg. The largest Cargo capacity is 9,000 kg on ATR 72-600 Freighter aircraft and the smallest is 2,150 on ATR 72-600 Passenger aircraft. If cargo delivery does not exceed 2,150 kg, it is more profitable to use ATR 72-600 passenger aircraft, but if the weight or volume sent much larger should use the ATR 72-600 Freighter.